USER INVOLVEMENT APPROACH IN AGILE SOFTWARE DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW - Qudrattullah Omerkhel; Othman Mohd Yusop; Saiful Adli Ismail; Azri Azmi (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This systematic literature review paper aims to identify and analyze the issues of managing users during requirement elicitation within agile software development (ASD) in the existing studies. The study employs a comprehensive search strategy to identify relevant articles published in peer-reviewed journals and conference proceedings. The findings reveal that the current literature focuses on various issues related to user involvement, communication, and collaboration during requirement elicitation. The paper identified 8 different issues related to managing users during requirement elicitation within ASD: user availability, lack of user involvement, long users’ feedback loops, lack of user expertise, ineffective product owner, lack of user communication skills, lack of process regarding user involvement, and lack of motivation. By identifying these issues, practitioners can overcome the issues of user involvement during requirement elicitation within ASD, and resolve conflicts to ensure a successful requirement elicitation process. The paper concludes by identifying the gaps in the existing literature and suggesting future research directions to address these gaps. The research provides valuable insights into the issues of managing users during requirement elicitation within ASD.